Respuesta :
Answer:
-10
Step-by-step explanation:
Note that you are subtracting two negative numbers. In this case, just carry over the negative sign, and add the numbers:
- 4 - 6 = - (4 + 6) = - (10) = -10
-10 is your answer.
~
Answer and Step-by-step explanation:
This question is quite simple if you see:
All you have to do is first, Remove the brackets then change those negative sign into the positive sign. (You may have learnt it in Integers)
when a minus and a minus is here in an expression it will change into a plus sign . [tex](--=+)[/tex]
So, It will be something like this :
[tex]4+6=-10[/tex]